Analisis Hardskill Mahasiswa Akuntansi Terhadap Kompetensi Auditor Era Revolusi Industri 4.0 - Nopi Hernawati; Mey Maemunah; Ririn Sri Kuntorini (Universitas Islam Bandung, 2021)
AbstractThe industrial revolution 4.0 can be an opportunity, challenge or threat for various professions including the auditor profession. One of the challenges that must be answered is technological disruption. If the auditors are not able to adapt, they are threatened with extinction. Accounting students as the forerunners of the auditor profession must prepare themselves to become competitive professional auditors. The purpose of this research is to answer the problem formulation and analyze the hardskills of accounting students in preparing for auditors' competence in the revolutionary era 4.0. The research method used is a case study with a descriptive analysis approach. Data collection techniques are observation, in-depth interviews and documentation. The results of this study indicate that accounting students have hard skills including accounting, finance and other related sciences, knowledge of business activities and organizing and Knowledge and competence in the field of information technology. Hard skills of accounting students have an effect on auditor competence. It is hoped that it can become an innovation that becomes a reference for the development of skills of accounting students in preparing for auditors' competence in the revolutionary era 4.0.Keywords: Accounting Student hardskill, auditor competency, Industry Revolution 4.0 Abstrak Revolusi industri 4.0 bisa menjadi peluang, tantangan maupun ancaman bagi berbagai profesi termasuk profesi auditor. Salah satu tantangan yang harus dijawab adalah disruptif teknologi, ika auditor tidak mampu beradaptasi, maka terancam akan punah. Mahasiswa akuntansi sebagai cikal bakal profesi auditor harus mempersiapkan diri untuk menjadi auditor profesional yang berdaya saing. Adapun tujuan yang akan dihasilkan dari penelitian ini adalah untuk menjawab perumusan masalah dan menganalisis hardskill mahasiswa akuntansi dalam mempersiapkan diri menghadapi kompetensi auditor era revolusi 4.0. Metode penelitian yang digunakan adalah studi kasus dengan pendekatan deskriptif analisis. Teknik pengumpulan data adalah observasi, wawancara mendalam dan dokumentasi. Hasil penelitian ini menunjukkan bahwa mahasiswa akuntansi telah memiliki hardskill diantaranya Ilmu akuntansi, keuangan dan ilmu pengetahuan terkait lainnya, pengetahuan mengenai kegiatan bisnis dan pengorganisasian, pengetahuan dan kompetensi di bidang teknologi informasi. Hardskill mahasiswa akuntansi berpengaruh terhadap kompetensi auditor. Diharapkan dapat menjadi inovasi yang menjadi referensi bagi pengembangan skill mahasiswa akuntansi dalam mempersiapkan diri menghadapi kompetensi auditor era revolusi 4.0.